Perceptions of governance effectiveness and fisheries restriction options in a climate refugia. (June 2020) - McClanahan, Tim; Abunge, Caroline
Abstract: Common-pool resources are challenged by a number of factors including broadly acceptable resource extraction restrictions and effective implementation of proposed restrictions. Consequently, we evaluated fisher's perceptions of effectiveness of their governance institutions and benefits of restrictions in 16 East African marine fishing communities. At this site level the mean perceived effectiveness of 10 governance institutions and benefits of six restrictions were positively related (r 2 = 0.57, p < 0.0007). However, this relationship masked governance-restriction dimensions that differentiated communities that perceive benefits of closures, protected areas, and species selection versus those preferring gear, minimum sizes of fish at capture, and closed season restrictions. The first "pro-conservation group" was distinguished by their higher scaling of the effectiveness of monitoring of resources and users, graduated sanctions, group identity, and decision-making. Consequently, stronger support for traditional area-and species-based conservation may require strengthening these institutions whereas traditional fisheries restrictions should find more support where these institutions are weaker. A climate refugia center that was a high priority for spatial management had strong support for closure restrictions in some sites but weak effectiveness of monitoring of resource users and ecology more broadly, which will need to be strengthened to insure successful area-based management. Highlights: Perceptions of governance effectiveness and fisheries restrictions were studied. Area and species conservation were most influenced by the strength of monitoring. Weak monitoring was associated with more support for fisheries restrictions. High heterogeneity of governance effectiveness found in the climate refugia Monitoring resources and users recommended to increase support for conservation.